Bad Boys Sick Girls Geschlecht und dissoziales Verhalten - Preuß, Ulrich (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2010)
Dissocial and delinquent behavior in adolescents is characterized by well-known significant gender differences in type and frequency that continue into adulthood. Although there has been an increase in delinquent behavior among girls in recent years, it remains to be seen what significance this phenomenon will have in the future. Why are male adolescents delinquent significantly more often than female adolescents? The contributions in this volume represent possible causes, the different course, the different consequences and the treatment options for the female or male adolescents. Two aspects come to the fore: - The neurobiological causes of delinquent behavior that are relevant in early childhood mainly concern male adolescents. - The social conditions of dissocial development have more impact on socialization in male delinquency; female adolescents have significantly more support for socially unobtrusive development in the social environment throughout their development. Delinquency in female adolescents is more often considered an expression of mental disorders. Although there is no causal factor, this also helps to reduce the number of girls and young women in crime statistics. This volume adequately analyzes the gender differences in delinquent behavior and is a must-read for all experts and those interested in youth delinquency.